Lan tỏa rủi ro đuôi giữa năng lượng tái tạo và thị trường chứng khoán các nước ASEAN-6 - Ngô Thái, Hưng; Nguyễn Khánh, An (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study aims to explore tail risk spillovers between renewable energy and the ASEAN-6 stock markets (Vietnam, Thailand, the Philippines, Indonesia, Malaysia, and Singapore) from January 2, 2018, to November 26, 2024. To achieve this, the authors employ the ADCC-GARCH model to estimate the tail risk spillover value (ΔCoVaR) between market pairs based on the CoVaR and ΔCoVaR approaches. Additionally, the quantile-based spillover connectedness is used to evaluate tail risk spillovers across all markets under different risk scenarios (high, medium, and low risk). The results provide evidence that negative shocks in the renewable energy market lead to higher risks in the stock markets but do not act as a primary transmitter of tail risk spillovers. Specifically, the highest levels of tail risk spillover are observed during periods of extreme market conditions and high risk.
Keywords: Renewable energy; Stock markets; Systemic risks; ASEAN-6